Penegakan Hukum Kasus Korupsi Dana Bos dan Peranan Badan Pemeriksa Keuangan (BPK) - Susilawati, Ni Putu Pebri; Saravistha, Deli Bunga; Aristiawan , I Gusti Ngurah (Indra Institute Research & Publication, 2024)
School Operational Assistance, or BOSS, is one of the programs initiated by the government aimed at improving the quality of education, both means and supplies, as well as expropriation affairs. It is in accordance with the mandate given to the Fifth Path of the ideology of the nation, namely Pancasila, “Social Justice for All the People of Indonesia.